Complete androgenin sensitivity syndrome presenting with primary amenorrhoea and inguinal mass: a case report - Saranya, P.; Pavani, S.; ., Ramalingam; Swaroopa, M. Mahima; Hari Babu, R. (International Journal of Research in Medical Sciences, 2020)
Androgen insensitivity syndrome (AIS), also known as testicular feminization, an X-linked recessive disorder comprises a wide range of phenotypes that are caused by various types of mutations in the androgen receptor gene. AIs can be classified as complete, partial, or mild based on the phenotypic presentation. The clinical findings include a female type of external genitalia, 46-XY karyotype, absence of Mullerian structures, presence of Wolffian structures to various degree, and normal to high testosterone and gonadotropin levels. We report this case as an interesting and rare syndrome. The patient is a 15-year-old phenotypic female who presented with primary amenorrhea and normal-appearing external genitalia. Orchidectomy was done after proper counselling and proper psychological support was given to her.